Rethinking growth through trade: a two-tiered capabilities approach - Martin, S (2018)
Trade has been a concern of global justice theorists since Charles Beitz prominently cited it as a fundamental cause of global inequalities in his seminal 1979 book Political Theory and International Relations. Yet it is only recently that theorists are beginning to address trade in and of itself. Following David Miller, I define trade as “a practice that involves the voluntary exchange of commodities or services for mutual advantage. That means, self-evidently, that both trading partners expect to be better off as a result of their exchange.” Ultimately, the problem is, that despite this definition of trade, it does not always benefit both partners or at the very least benefit them to the full (expected) potential of the exchange. That is, trade, quite problematically, does not fulfill its normative potential; it is not doing what it was designed to do.